2021
DOI: 10.1021/acsami.1c12393
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Durability of Lithium-Metal Anode via In situ Constructed Multilayer SEI

Abstract: In this work, a novel multilayer solid electrolyte interphase (SEI) is demonstrated to prolong the durability of a lithium-metal anode. It is in situ generated via reducing lithium bis­(oxalate) borate (LiBOB) and fluoroethylene carbonate (FEC) in the electrolyte containing them as additives. The as-obtained SEI could be roughly divided into three layers: the polycarbonates surface membrane, LiF-rich middle layer, and B-containing polymer bottom film corresponding to their sequentially reductive potentials of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Essentially, Li dendritic growth involves the transmission and electrochemical reduction of Li + , which is a classic metal electrodeposition phenomenon. The nonuniform lithium deposition is the root cause of the above problems. Many efforts have been made to tackle matters to achieve dendrite-free LMBs, including optimizing electrolytes, , designing an artificial SEI film, building a functional separator, constructing an internal electric field or external magnetic field, , designing a three-dimensional (3D) host, and so on. Cui et al provided insight into the nucleation and deposition process of Li metal on diverse substrates and concluded that certain substrates such as Au, Ag, Zn, and Sn can guide a homogeneous Li deposition with few nucleation barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, Li dendritic growth involves the transmission and electrochemical reduction of Li + , which is a classic metal electrodeposition phenomenon. The nonuniform lithium deposition is the root cause of the above problems. Many efforts have been made to tackle matters to achieve dendrite-free LMBs, including optimizing electrolytes, , designing an artificial SEI film, building a functional separator, constructing an internal electric field or external magnetic field, , designing a three-dimensional (3D) host, and so on. Cui et al provided insight into the nucleation and deposition process of Li metal on diverse substrates and concluded that certain substrates such as Au, Ag, Zn, and Sn can guide a homogeneous Li deposition with few nucleation barriers.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure b, both Si and Si@PPA-7% anodes show alloying and de-alloying processes. However, from the partially enlarged curves, it can be found that the Si electrode has an obvious side reaction peak at 1.48 V, corresponding to the decomposition reaction of the FEC-based electrolyte, while the peak disappears in the Si@PPA-7% electrode, showing that the decomposition reaction is effectively inhibited by the PPA interface layer, and thus the increased ICE of the Si@PPA anodes is obtained. In addition, the oxidation peaks of the Si@PPA-7% electrode are slightly more noticeable, which can also be detected clearly in the following cycles (Figure S4), suggesting that the PPA layer can accelerate the de-alloying phase transformation reaction.…”
Section: Resultsmentioning
confidence: 98%
“…Although these methods are successful in prolonging the lifespan of the Li metal anode, they are complicated in manufacture and cannot avoid the disintegration of the artificial protective films and electrolytes. In contrast, the approach of adding additives to electrolytes is more facile and effective to construct an in situ protective layer. Wang et al proposed an ionic liquid additive to fabricate an organic/inorganic ordered dual-structure layer on the lithium surface, which suppresses dendrite formation and improves the Coulombic efficiency of the lithium metal . In our previous work, an in situ multilayer protective film was constructed by coadditives.…”
Section: Introductionmentioning
confidence: 99%
“…20−22 Wang et al proposed an ionic liquid additive to fabricate an organic/ inorganic ordered dual-structure layer on the lithium surface, which suppresses dendrite formation and improves the Coulombic efficiency of the lithium metal. 23 the cracks of the LiF-rich layer and prolong the lifespan of the lithium anode effectively. 24 However, these films were still unstable in the long cycling, which might be due to their insufficient lithiophilic property, and tend to be exfoliated from the anode.…”
Section: ■ Introductionmentioning
confidence: 99%